1969
DOI: 10.1042/bj1130057
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of camphors and related compounds

Abstract: 1. The metabolism of (+/-)-norcamphor, (+)-camphor, (-)-camphor, (+)-epicamphor, (+/-)-camphorquinone, (+/-)-camphane-2,5-dione and camphane was investigated in rabbits. All the compounds except camphane-2,5-dione increased the content of glucuronide in the urine. 2. (+/-)-Norcamphor was reduced to endo-norborneol; (+)-camphor, contrary to expectation, was reduced to (+)-borneol, as well as being hydroxylated to (+)-5-endo-hydroxycamphor and (+)-3-endo-hydroxycamphor, 5-endo-hydroxycamphor being the predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Asahina and Ishidate (1933;1934;1935) isolated cis-and trans-π-hydroxycamphor and camphor-π-carboxylic acid from the urine of dogs that had been fed with camphor; Shimamoto obtained 3-hydroxycamphor (15%), 5-hydroxycamphor (55%) and trans-π-hydroxycamphor (20%) from the urine of dogs, and 5-hydroxycamphor [as major metabolite] and 3-hydroxycamphor from the urine of rabbits (Shimamoto, 1934). Robertson and Hussain (1969) observed that (+)-camphor and (-)-camphor increase the content of glucuronide in the urine of rabbits; (+)-camphor was moreover reduced to (+)-borneol as well as being hydroxylated to (+)-5-endo-hydroxycamphor [major product] and (+)-3-endo-hydroxycamphor. Hydroxylation of camphor, as well as norcamphor, pericyclocamphanone and 5,5-difluorocamphor, is mainly performed by Cytochrome P-450 (Collins and Loew, 1988), a class of heme-containing monooxygenases that are distributed in the whole body (Boxenbaum, 1984), by hydrogen abstraction (Wand and Thompson, 1986).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Asahina and Ishidate (1933;1934;1935) isolated cis-and trans-π-hydroxycamphor and camphor-π-carboxylic acid from the urine of dogs that had been fed with camphor; Shimamoto obtained 3-hydroxycamphor (15%), 5-hydroxycamphor (55%) and trans-π-hydroxycamphor (20%) from the urine of dogs, and 5-hydroxycamphor [as major metabolite] and 3-hydroxycamphor from the urine of rabbits (Shimamoto, 1934). Robertson and Hussain (1969) observed that (+)-camphor and (-)-camphor increase the content of glucuronide in the urine of rabbits; (+)-camphor was moreover reduced to (+)-borneol as well as being hydroxylated to (+)-5-endo-hydroxycamphor [major product] and (+)-3-endo-hydroxycamphor. Hydroxylation of camphor, as well as norcamphor, pericyclocamphanone and 5,5-difluorocamphor, is mainly performed by Cytochrome P-450 (Collins and Loew, 1988), a class of heme-containing monooxygenases that are distributed in the whole body (Boxenbaum, 1984), by hydrogen abstraction (Wand and Thompson, 1986).…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Metabolites in rabbit liver microsomes were similar to those obtained in the analogous rat liver microsomes, except that the ratio of endo-and exo-isomers of 5-hydroxycamphor produced from camphor was higher than in the rat liver preparation. 3,4) In human liver microsomes, 5-exo-hydroxycamphor was detected only an oxidation product. These results suggested that there are species-related differences in the metabolism of camphor to 3-hydroxycamphor, 5-exo-and 5-endo-hydroxycamphor by P450 enzymes in rats, rabbits and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of (Ϫ)-camphor in mammals, microorganism and plant cells have been published, e.g. dogs, 3,4) rabbits, 4) Pseudomonas putida, [5][6][7][8][9][10][11] Streptomyces griseus 12) the S. officinals [13][14][15] and Eucalyptus perriniana. 16) We recently established the biotransformation of (ϩ)-and (Ϫ)-camphor by Spodoptera litura (a species of caterpillar).…”
mentioning
confidence: 99%
“…Rabbits gavaged with 1.9 -3.5 mmol/kg bw [289 -533 mg/kg bw] d-camphor excreted 59.1 % of the dose conjugated with glucuronic acid in the urine within 24 hours (Robertson and Hussain, 1969). A group of 50 Sprague-Dawley rats was administered a single dose of 1,000 mg of 40 % camphor in cottonseed oil/kg bw (approximately 400 mg camphor) by gavage and killed at 0.25, 0.5, 0.75, 1.0, 1.5, 2.0, 4.0, 6.0, 8.0 or 10.0 hours following treatment.…”
Section: Iii21 Hydrolysis Of Estersmentioning
confidence: 99%